2009
DOI: 10.1016/j.abb.2009.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of glutathione reductase inhibition on cellular thiol redox state and related systems

Abstract: Although inhibition of glutathione reductase (GR) has been demonstrated to cause a decrease in reduced glutathione (GSH) and increase in glutathione disulfide (GSSG), a systematic study of the effects of GR inhibition on thiol redox state and related systems has not been noted. By employing a monkey kidney cell line as the cell model and 2-acetylamino-3-[4-(2-acetylamino-2-carboxy-ethylsulfanylthio-carbonylamino)phenylthiocarbamoylsulfanyl]propionic acid (2-AAPA) as a GR inhibitor, an investigation of the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
50
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 36 publications
1
50
1
Order By: Relevance
“…GSH is an important antioxidant agent that protects the cells from oxidative stress (31). After VSMCs were treated with MG for 24 h, cellular GSH level was significantly increased correspondingly to the concentrations of MG (10-50 mM) (Fig.…”
Section: Gsh Cysteine and Homocysteine Levels In Mg-or Nahs-treatedmentioning
confidence: 94%
See 1 more Smart Citation
“…GSH is an important antioxidant agent that protects the cells from oxidative stress (31). After VSMCs were treated with MG for 24 h, cellular GSH level was significantly increased correspondingly to the concentrations of MG (10-50 mM) (Fig.…”
Section: Gsh Cysteine and Homocysteine Levels In Mg-or Nahs-treatedmentioning
confidence: 94%
“…cells (31). GSH levels are significantly elevated when the cells are treated with MG (10, 30, and 50 mM) compared to that of the control group.…”
mentioning
confidence: 95%
“…In neurons, the decrease in ATP levels could be due to a reduction in NADH generation in mitochondria caused by the damage to KGDHC and aconitase and/or some other unidentified catabolic enzymes. In addition, the elevation of NADPH could have been caused by an increased production via Pentose Phosphate Pathway (30) and/or by an inhibition of Glutathione Reductase (GR) (70). Indeed, it has been reported that the low glycolytic rate in neurons results in increased flux through the pentosephosphate pathway, thus providing NADPH necessary to regenerate antioxidant glutathione (30).…”
mentioning
confidence: 99%
“…1A). Similarly, an inhibitor of glutathione reductase, 2-acetylamino-3-[4-(2-acetylamino-2-carboxyethylsulfanyl thiocarbonylamino) phenylthiocarbamoylsulfanyl] propionic acid (2-AAPA), which increases GSH-protein adducts (14), increased HIF-1α protein levels (Fig. S1).…”
Section: Resultsmentioning
confidence: 99%